2022
DOI: 10.3389/fcvm.2021.791646
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Interplay of Inflammation, Metabolism, Epigenetics, and Sex in Calcific Disease of the Aortic Valve

Abstract: Calcification of the aortic valve is one of the most rapidly increasing pathologies in the aging population worldwide. Traditionally associated to cardiovascular risk conditions, this pathology is still relatively unaddressed on a molecular/cellular standpoint and there are no available treatments to retard its progression unless valve substitution. In this review, we will describe some of the most involved inflammatory players, the metabolic changes that may be responsible of epigenetic modifications and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 123 publications
0
11
0
Order By: Relevance
“…Once an estimate told that the hazard of AS increases by 75% for each decade increase in age ( 20 ). As life expectancy remains increasing, inevitably, the burden of AS is anticipated to surge ( 21 ). Globally, male individuals were more likely to suffer from CAVD than female individuals with higher prevalence cases, death cases, DALYs, and corresponding age-standardized rates ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Once an estimate told that the hazard of AS increases by 75% for each decade increase in age ( 20 ). As life expectancy remains increasing, inevitably, the burden of AS is anticipated to surge ( 21 ). Globally, male individuals were more likely to suffer from CAVD than female individuals with higher prevalence cases, death cases, DALYs, and corresponding age-standardized rates ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, female individuals tended to present more fibrotic remodeling and less calcification than male individuals ( 22 ). Meanwhile, female individuals showed a more advanced age of onset of the disease ( 21 ). Studies focused on sex-specific features implied that the progression, pathophysiology, and hemodynamic severity of aortic valve calcification varied in males and females ( 23 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of new therapies for AVS has been impeded by a limited understanding of the complex mechanisms driving CAVD initiation and progression towards clinically relevant interventions. One of the first events triggering CAVD is the damage of the endothelium on both sides of the valve leaflets, resulting from local alterations of blood shear stress [ 6 ]. It has recently been shown that the valvular endothelial cells (VECs) and valvular interstitial cells (VICs) cultured in a gelatin methacrylate 3D construct and exposed to high glucose conditions presented increased expressions of various cytokines, cell adhesion molecules and matrix metalloproteinases, with a rapid and strong response in VECs, while in VICs the chronic inflammation developed and persisted longer [ 7 ].…”
Section: Introductionmentioning
confidence: 99%